Media Sosial dan Digitalisasi Partisipasi Politik pada Generasi Muda: Perspektif Indonesia: The Social Media and Digitalization of Political Participation in Youths: An Indonesian Perspective - Muhammad Saud; Rachmah Ida; Ansar Abbas; Asia Ashfaq; Araz Ramazan Ahmad (Society, 2020)
Digitalization in the modern era has provided opportunities for the youths to participate in this information and social spheres. The concentrated use of social media has contributed to the astonishing factor among the voters where social media has changed the preferences of youths toward the right to vote. The research aims to investigate the contributions and preferences of youths toward political participation in the contemporary discussion in Indonesia. This research was quantitative research using a purposive random sampling technique to give equal opportunity to each respondent. The mode of data collection was an online survey. The majority of the respondents in this research were the student of the universities. Data were collected in April 2019 to examine the interest of youths in general elections in Indonesia. This research found that social media and Social Networking Sites (SNSs) have provided a unique platform to discuss political matters and ‘take apart’ in political discussions. Existing in-depth researches on this phenomenon show that political awareness among youths in Indonesia is an essential part and social media is the leading indicator. This research suggested some recommendations for to usage of social media for the socialization of youths.